2020
DOI: 10.1101/2020.06.10.20115543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of 30-day mortality for 500 patients undergoing non-emergency surgery in a COVID-19 cold site within a multicentre regional surgical network during the COVID-19 pandemic

Abstract: Background Two million non-emergency surgeries are being cancelled globally every week due to the COVID-19 pandemic, which will have a major impact on patients and healthcare systems. Objective To determine whether it is feasible and safe to continue non-emergency surgery in the COVID-19 pandemic Design, setting and participants This is a cohort study of 500 consecutive patients undergoing non-emergency surgery in a dedicated COVID-19 cold site following the first case of COVID-19 that was reported in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…(9) The ‘cold’ site model has been safely described elsewhere, and reports from another ‘cold’ site in London have reported a 2% rate of post-operative COVID-19 infection, with only 0.2% of their cohort reporting Clavien-Dindo grade 3 complications related to COVID-19. (10) The current study supports the practice of ‘cold’ sites in areas still suffering from high rates of COVID-19.…”
Section: Discussionsupporting
confidence: 78%
“…(9) The ‘cold’ site model has been safely described elsewhere, and reports from another ‘cold’ site in London have reported a 2% rate of post-operative COVID-19 infection, with only 0.2% of their cohort reporting Clavien-Dindo grade 3 complications related to COVID-19. (10) The current study supports the practice of ‘cold’ sites in areas still suffering from high rates of COVID-19.…”
Section: Discussionsupporting
confidence: 78%
“…It would provide enhanced system resilience in the context of future COVID-19 outbreaks to continue planned surgery in dedicated clean sites. 8 26 27 The scheme may have additional benefits including increased patient choice, greater workforce flexibility and maximisation of teams across areas, with increasing efficiency. There is a paucity of high-quality data on the effects of pooled waiting-lists.…”
Section: Discussionmentioning
confidence: 99%
“…Another study that assessed the feasibility of nonemergency surgery in a COVID-19 cold site during the pandemic demonstrated that out of 500 patients only 10 (2%) had COVID-19 infection post-operatively. 14 Three patients (1%) passed away within 30 days of surgery; however, no mortality was noted due to COVID-19 infection. Grade 3 or more Clavien-Dindo complications were recorded in 33 patients (7%) overall and in only one patient (3%) with post-operative COVID-19 infection.…”
Section: The Risks For Patients Undergoing Surgerymentioning
confidence: 91%